The Neglected Poetry (2019)
This book collects for the first time a compendium of poems written in English by brigadists, sanitary personnel and journalists that participated or were involved in the Spanish Civil War, as well as by intellectuals, writers and journalists that supported the republican cause from the outside. The anthology starts from a previous historical framework in which this poetic legacy has been contextualized, to know where, when, how and why these poems were written, and who wrote them or who were their protagonists. All these analyses have served to understand the causes of why this poetic legacy has been denied and has not received the recognition it deserves today.Este libro recoge por primera vez un compendio de poemas escritos en inglés por brigadistas, personal sanitario y periodistas que participaron o estuvieron involucrados en la Guerra Civil española, así como por intelectuales, escritores y periodistas que apoyaron la causa republicana desde el exterior. La antología parte de un marco histórico anterior en el que se ha contextualizado este legado poético, para saber dónde, cuándo, cómo y por qué se escribieron estos poemas, y quiénes los escribieron o quiénes fueron sus protagonistas. Todos estos análisis han servido para comprender las causas de por qué este legado poético ha sido negado y no ha recibido el reconocimiento que hoy merece.
Keywords: Poemas; Guerra Civil española; Antología poética